An Interesting Case of Influenza A in A Patient with Severe Neurosarcoidosis Mimicking A Neurosarcoid Flare - Hassan, Romesa Sajjad; Pasham, Ashwariya; Ahmed, Samreen; Wu, Victoria; Saran, Nitu; Tavee, Jinny O.; Ascoli, Christian; Sweiss, Nadera (Archives of Clinical and Medical Case Reports, 2024)
Sarcoidosis is a multisystem disease with involvement of the nervous system occurring in about 5-10 % of patients. Neurosarcoidosis most commonly affects cranial nerves but can also involve other nervous system tissues including meninges, brain parenchyma, spinal cord and peripheral nerves. This is an interesting case of a 51-year-old woman with a history of neurosarcoidosis with known involvement of brain parenchyma and cervical spine who presented with severe and symptomatic hyponatremia. She was found to have Influenza A complicated with superimposed bacterial pneumonia. In the absence of a previous history of chronic hyponatremia, endocrine or renal abnormalities we suspect the hyponatremia to be secondary to SIADH likely caused by Influenza A and bacterial pneumonia infections and less likely due to Neurosarcoidosis. We believe neurosarcoidosis is a less likely etiology in our case since our patient had Neurosarcoidosis for 4 years but severe, symptomatic hyponatremia of this sort was never reported since the time of diagnosis. The possible mechanisms of influenza A virus, the novel coronavirus (SARS-COV-2) or other viral infections causing hyponatremia are discussed in detail. Also, we believe that evaluation of altered mental status or any other neurologic dysfunction in a patient with Neurosarcoidosis should be thorough and other etiologies including infectious or endocrine causes should be highly considered. This case also highlights the importance of seasonal vaccinations especially in sarcoidosis patients to avoid such complications.